Leadership style in enhancing employees' competency for organizational performance in food industries - Atan, Jamsari (2021)
In 2016, the productivity performance level of Malaysian employees was rather low and lagged behind other countries, while the organizational performances of several major food manufacturing industries in Malaysia were also found to be declining. In the same vein, the world's biggest economies and Malaysia are at present suffering from high employee turnover, low levels of innovation, customer complaints, and lack of employee competency. This study examines the role of transformational and transactional leadership style as practiced by the organizational leaders of food manufacturing industries in Johor, Malaysia in enhancing the organizational performance through employee competencies. Three prominent food manufacturing industries in Malaysia were selected for this research. The sample of the study comprised of 232 employees from various supervisory levels in various departments and sections within the production line. Seven hypotheses with a conceptual model were developed and tested based on the previous literature review. The SmartPLS version 3.0 was applied to evaluate the measurement models, structural models, and mediation models for this study. The result of the PLS-SEM analysis confirmed that the transformational and transactional leadership style and employee competencies had contributed to the organizational performance significantly. The mediation analysis results found that employee competencies partially mediated the relationship between transformational and transactional leadership styles and organizational performance. The statistical results, besides indicating the suitability of the PLS-SEM in this study, contributed to an understanding of the role of leadership style in enhancing employee competencies and organizational performance in the food manufacturing industries, thus adding to the body of knowledge. The result of this study provided useful information to other Malaysian organizations to identify ways to improve the organizational performance and profitability in supporting the aim of the Ministry of International Trade and Industry Malaysia (MITI) to increase Malaysia's economic growth as envisioned by the Malaysian Government through the National Key Result Areas (NKRA).